2021
DOI: 10.3390/s21103481
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Prediction of Fall Risk in Older Adults Using Timed Up and Go Test Kinematics

Abstract: Falls among the elderly population cause detrimental physical, mental, financial problems and, in the worst case, death. The increasing number of people entering the higher risk age-range has increased clinicians’ attention to intervene. Clinical tools, e.g., the Timed Up and Go (TUG) test, have been created for aiding clinicians in fall-risk assessment. Often simple to evaluate, these assessments are subject to a clinician’s judgment. Wearable sensor data with machine learning algorithms were introduced as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 27 publications
1
33
1
2
Order By: Relevance
“…The result of subjects classification gives the accuracy of 87.5%. These results are better than some of the results obtained with similar research [23], while using the smaller number of sensors. It should also be noted that the study group revealed only very subtle balance and gait abnormalities in the clinical examination.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The result of subjects classification gives the accuracy of 87.5%. These results are better than some of the results obtained with similar research [23], while using the smaller number of sensors. It should also be noted that the study group revealed only very subtle balance and gait abnormalities in the clinical examination.…”
Section: Discussioncontrasting
confidence: 73%
“…With regard to research concerning the use of CNNs to analyse IMU data, Roshdibenam et al proposed a solution for detecting risk of falls in elders using CNN model with the raw kinematics signal. The signal was obtained during the TUG test from proprietary IMU sensors, developed in MEMS technology, placed on the neck and feet [23]. The CNN model was using three seconds time series segments as the input, multiple deep layers and binary output distinguishing faller from non-faller.…”
Section: State Of the Artmentioning
confidence: 99%
“…Apesar de autores considerarem essa análise ainda limitada e influenciada por outras variáveis, estudo retrospectivo evidenciou associação significativa positiva entre o tempo de realização do teste e histórico de quedas em idoso. Além disso, o teste foi relatado como de sensibilidade considerável quando se trata de idosos com dependência funcional (Roshdibenam, et al, 2021).…”
Section: Discussionunclassified
“…All subjects were sent questionnaires 6 to12 months (mean for all subjects was 9 months) following clinic evaluation to query if they had fallen since the initial evaluations. The inertial measurement data were stored for use in a follow-up experiment reported elsewhere [ 9 ].…”
Section: Methodsmentioning
confidence: 99%